Etude et analyse des performances d'un réseau optique passif large bande bidirectionnel (BPON) - قديري, لزهر; بدادة, ايمن (University of El Oued جامة الوادي, 2018)
الطلب على القدرات المرتبطة بنقل جميع أنواع المعلومات (الصوت والفيديو والبيانات وما إلى ذلك) في نمو مستمر. ولضمان هذا النمو، سرعة التدفق يجب ان تتطور بنفس السرعة، بما في ذلك في الكيلومترات الأخيرة التي تربط المستخدمين، والتي نسميها شبكات الوصول. نتيجة لذلك، دخلت البصريات بيوتنا في السنوات الأخيرة، من خلال وصلات عالية التدفق (الليف حتى المنزل). العديد من التكنولوجيات سخرت لإيصال الألياف البصرية إلى المشترك وسنركز بشكل خاص على الحل المتمثل في الشبكات البصرية الخاملة. الهدف من هذا المشروع هو دراسة ومحاكاة شبكة ثنائية الاتجاه لعدة مستعملين وبمعدل نقل 622 ميجا/الثانية في كلا الاتجاهين. The demand for capacity related to the transmission of all types of information (voice, video, data, etc.) are continues to grow. In order to ensure this growth, the transmission rate must evolve at the same speed, including in the last kilometers connecting the users, which we call the access networks. As a result, optics has entered our homes in recent years, through the very high speed FTTH (Fiber to the Home) links. Several techniques are distinguished to bring the fiber to the subscriber and we will focus particularly on the solution PON (Passive Optical Networks). The objective of this project is to study and simulate a bidirectional(4/8 et 16 users BPON network with a flow of 622 Mb/s in both directions upstream and downstream.
مذكرة ماسترهندسة كهربائية تخصص اتصالات
Keywords: Optical fiber, Access networks, FTTx,High speed transmission.; الليف البصري، شبكة النفاذ، FTTx، الارسال ذو التدفق العالي